Insurance motives to remit: Evidence from a matched sample of Ethiopian internal migrants - de Brauw, Alan; Mueller, Valerie; Woldehanna, Tassew (International Food Policy Research Institute, 2011)
Migration and remittances can be used by rural households as a means of insurance, investment, and income augmentation. Ample attention has been given to studying international remittance flows, since for many countries such transfers comprise a significant fraction of income. Remittance flows from internal migrants are relatively understudied, particularly in Africa, where remittance rates are poor. We use a unique matched migrant sample to study what drives the low remittance rates in Ethiopia. Descriptive statistics suggest remitters are positively selected in terms of wealth characteristics compared with the average tracked migrant. Limited skill transferability and liquidity largely explain low remittance rates in Ethiopia. Weaker evidence suggests migrants are additionally motivated to remit as a form of self-insurance against own shocks to income and investments towards future inheritable assets.